Osthenol Shows Cardioprotective Activity Against Isoproterenol-Induced Myocardial Infarction in Rats via Inhibiting Oxidative Stress and Inflammation - Wei, Liu; Quanbao, Wen (Indian Journal of Pharmaceutical Education and Research, 2018)
Background: Myocardial Infarction (MI) is a devastating cardiovascular complication that develops when blood flow to a region of the myocardium is obstructed, resulting in cardiomyocyte necrosis and loss of contractile function. Objectives: This study was intended to assess the cardioprotective activity of the osthenol against Isoproterenol (ISO)-induced MI in rat model. Materials and Methods: The Sprague-Dawley rats were subjected to ISO administration to develop MI and were pre- and co-treated with osthenol for 20 days. The standard drug amlodipine was pre-treatment for 20 days. Upon completion, the Systolic Blood Pressure (SBP) and heart rate was analyzed utilizing rat tail-cuff plethysmography. The concentrations of cardiac injury biomarkers, oxidative stress markers, and inflammatory biomarkers were examined utilizing the commercial kits. The cardiac tissues were collected and subjected to histopathological investigation to assess histological alterations. Results: The current findings demonstrated that osthenol treatment significantly reduced both SBP and heart rate levels in ISO-treated rats. The cardiac injury biomarkers, pro-inflammatory biomarkers, and lipid peroxidation marker were significantly reduced by osthenol treatment in ISO-treated rats. Furthermore, osthenol treatment considerably elevated the antioxidants in the rats with MI. Moreover, the administration of osthenol significantly mitigated the histological changes in the heart of MI rats. Conclusion: The present findings demonstrate that osthenol treatment can mitigate and protect against the biochemical and histological alterations in rat cardiac tissues caused by ISO, because of its antioxidant and anti-inflammatory activities. Thus, osthenol may represent a novel therapeutic option to treat MI.
Keywords: Creatine kinase-MB; Myocardial infarction; Osthenol; Interleukin-6; Heart rate